2020
DOI: 10.1590/1678-4324-2020190408
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Green Propolis: Chemical Composition of Essential Oil and Their In Vitro Antioxidant, Antibacterial and Antiproliferative Activities

Abstract: Propolis is a resinous substance collected and processed by Apis mellifera from parts of plants, buds and exudates. In Minas Gerais (MG) state, Brazil, green propolis is produced from the collection of resinous substance found in shoot apices of Baccharis dracunculifolia. This paper aims to investigate the chemical composition and in vitro antioxidant, anti-Helicobacter pylori, antimycobacterial and antiproliferative activities of essential oil (EO) from Brazilian green propolis (BGP-EO). The oil showed high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…In other studies, the major compounds were thymol (29.61%), its isomer carvacrol (30.57%) from Kermanshah City in the west of Iran [ 34 ], carvone (40.34%), β-bisabolene (10.6%), β-thujone (11.45%), carvone (40.34%) from Tehran Province, Iran [ 35 ], carvacrol (20.7%), acetophenone (13.5%), spathulenol (11.0%), ( E )-nerolidol (9.7%), β-caryophyllene (6.2%) from Atlantic Forest in São Lourenço MG, Brazil [ 36 ], β-pinene (2.0–21.8%), α-pinene (1.2–46.5%), limonene (11.6%), dihydrosabinene (17.8%), 1 , 8 -cineole (0.1–11.0%), p -cymene (0.1–5.3%), 2 , 7 -dimethyl- 3 -octen- 5 -yne (trace-11.7%), octanal (12.9%), ( E )-β-ocimene (17.8%), α-thujene (trace-11.0%), and styrene (13.5%) from South Africa [ 37 ], δ-cadinene (1.29–13.31%), γ-cadinene (1.36–8.85%) and α-muurolene (0.78–6.59%), β-eudesmol (2.33–12.83%), T-cadinol (2.73–9.95%) and α-cadinol (4.84–9.74%) from different Italian regions [ 19 ], and α-pinene, β-pinene, γ-terpinene, α-muurolene, γ-cadinene and δ-cadinene from different regions of Croatia [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, the major compounds were thymol (29.61%), its isomer carvacrol (30.57%) from Kermanshah City in the west of Iran [ 34 ], carvone (40.34%), β-bisabolene (10.6%), β-thujone (11.45%), carvone (40.34%) from Tehran Province, Iran [ 35 ], carvacrol (20.7%), acetophenone (13.5%), spathulenol (11.0%), ( E )-nerolidol (9.7%), β-caryophyllene (6.2%) from Atlantic Forest in São Lourenço MG, Brazil [ 36 ], β-pinene (2.0–21.8%), α-pinene (1.2–46.5%), limonene (11.6%), dihydrosabinene (17.8%), 1 , 8 -cineole (0.1–11.0%), p -cymene (0.1–5.3%), 2 , 7 -dimethyl- 3 -octen- 5 -yne (trace-11.7%), octanal (12.9%), ( E )-β-ocimene (17.8%), α-thujene (trace-11.0%), and styrene (13.5%) from South Africa [ 37 ], δ-cadinene (1.29–13.31%), γ-cadinene (1.36–8.85%) and α-muurolene (0.78–6.59%), β-eudesmol (2.33–12.83%), T-cadinol (2.73–9.95%) and α-cadinol (4.84–9.74%) from different Italian regions [ 19 ], and α-pinene, β-pinene, γ-terpinene, α-muurolene, γ-cadinene and δ-cadinene from different regions of Croatia [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Como marcador principal, tem-se a molécula de artepilina C, um importante antioxidante, e ainda conta com derivados do ácido p-cumárico e diterpenos. É considerada uma das própolis mais estudadas no âmbito científico (Cavalaro, 2017;Quintino, et al, 2020).…”
Section: Resultsunclassified
“…Jug et al (2014) also evaluated the antibacterial and antifungal efficiency of green propolis extracts obtained by different extraction techniques and demonstrated that the ethanolic extract showed the best antimicrobial action. Quintino et al (2020) verified the antimicrobial activity of the oil extracted from fresh green propolis (Figure 11), with carvacrol being the compound with the highest concentration (20.7%), finding a MIC of 6.25 μg/ml against Helicobacter pylori, 62.5 μg/ml against Mycobacterium avium and 64 μg/ml for Mycobacterium tuberculosis (Quintino et al, 2020). Tomazzoli et al (2021) analyzed the antioxidant activity of the essential oil of fresh leaves of B. dracunculifolia collected in ten locations in Paraná -Brazil.…”
Section: Green Propolismentioning
confidence: 99%
“… Antimicrobial activity of the oil extracted from B. dracunculifolia green propolis ( Quintino et al, 2020 ). …”
Section: Pharmacology and Bioactivitymentioning
confidence: 99%